2011
DOI: 10.1111/j.1439-0396.2011.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of excess cobalt on milk fatty acid profiles and transcriptional regulation of SCD, FASN, DGAT1 and DGAT2 in the mammary gland of lactating dairy cows

Abstract: The main objective of this study was to investigate the effect of excess cobalt (Co) on gene expression of stearoyl-CoA desaturase (SCD), fatty acid synthase (FASN), diacylglycerol acyltransferase 1 (DGAT1) and diacylglycerol acyltransferase 2 (DGAT2) of lactating dairy cows in relation to milk fatty acid profile. Seven multiparous cows of the Norwegian Red cattle breed (NRF) had their basal diet supplemented with 1.4 g Co as a 24 g/l solution of Co-acetate per os twice daily for 7 days followed by a 9-day dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 41 publications
2
23
2
1
Order By: Relevance
“…Administration of Co has been demonstrated to decrease milk concentration of FA containing a cis-9 double bond in lactating cows (Shingfield et al, 2008;Taugbøl et al, 2008;Karlengen et al, 2012) and sows (Karlengen et al, 2011) but no reports exist for sheep. Preliminary assays conducted by the current authors suggested that changes in ovine milk FA composition to Co were less pronounced than that reported in cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of Co has been demonstrated to decrease milk concentration of FA containing a cis-9 double bond in lactating cows (Shingfield et al, 2008;Taugbøl et al, 2008;Karlengen et al, 2012) and sows (Karlengen et al, 2011) but no reports exist for sheep. Preliminary assays conducted by the current authors suggested that changes in ovine milk FA composition to Co were less pronounced than that reported in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies discovered rather serendipitously that administration of Co in the form of Co-EDTA (Shingfield et al, 2008) or Co acetate (Taugbøl et al, 2008;Karlengen et al, 2012) to lactating cows decreased milk fat concentrations of FA containing a cis-9 double bond. Intramuscular injections of Co acetate were also reported to induce similar changes in milk fat composi-tion in lactating sows (Karlengen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Oleic acid (18:1) is the most abundant mono-unsaturated fatty acid, and C18:2 is the most abundant poly-unsaturated fatty acid in cow milk (Månsson 2008). SCD is known to convert SFA (C16:0 and C18:0) to mono-unsaturated fatty acids (C16:1 and C18:1) by addition of a cis-double bond to fatty acyl-coenzyme A substrates (Miyazaki & Ntambi 2003;Mauvoisin & Mounier 2011;Karlengen et al 2012). Propionate increased the proportion of monounsaturated fatty acid (C16:1) and (C18:1) at the expense of decreased SFA (16:0) and (18:0).…”
Section: Scfa Regulate Lipogenesis In Goats 245mentioning
confidence: 99%
“…Such difference in response could be explained by the stronger effect on SCD1 expression with propionate than either butyrate or acetate treatment. SCD is known to convert SFA (C16:0 and C18:0) to mono-unsaturated fatty acids (C16:1 and C18:1) by addition of a cis-double bond to fatty acyl-coenzyme A substrates (Miyazaki & Ntambi 2003;Mauvoisin & Mounier 2011;Karlengen et al 2012). The alteration of unsaturated fatty acid composition appears largely due to marked upregulation of SCD1 by propionate.…”
Section: Scfa Regulate Lipogenesis In Goats 245mentioning
confidence: 99%
“…In particular, the high response of milk trans-9, trans-11-CLA in goats receiving sunfl ower oil could play a direct role in the typical decrease of milk FA desaturation ratios in this animal species (Table 13.2 ). Otherwise, abomasal infusions in cows and ewes (Griinari et al 2000 ;Corl et al 2001 ;Kay et al 2004 ;Bichi et al 2012 ) of sterculic oil, known as a strong inhibitor of SCD, and administration of Co-EDTA in the rumen or per os (Shingfi eld et al , 2008aTaugbøl et al 2008Taugbøl et al , 2010Karlengen et al 2012 ) decreased the milk FA desaturation ratios without alteration of mammary SCD1 mRNA abundance (Karlengen et al 2012 ) and without decreasing milk fat secretion. It was hypothesized (Shingfi eld et al 2008a ) that Cobalt interferes with the transfer of electrons from cytochrome b5 to the di-iron protein center of the terminal desaturase protein, thus altering the oxidation-reduction reactions of the conversion of the acyl-CoA substrates.…”
Section: In Vivo Studies With Specifi C Fatty Acid Infusion or Injectionmentioning
confidence: 99%